Pengaruh Materi Sekolah Minggu terhadap Perilaku Sekolah Minggu di GKPS Marubun Lokkung Tahun 2025 - Thabita Mutiara; Nisma Simorangkir; Dorlan Naibaho; Ibelala Gea; Raikhapoor Raikhapoor (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The research aims to determine the influence of Sunday school materials on Sunday school behavior at GKPS Marubun Lokkung in 2025. The research hypothesis is that there is a positive influence between Sunday school materials on Sunday school behavior at GKPS Marubun Lokkung in 2025. Descriptive quantitative research method. The total population of Sunday school children aged 8-11 years at GKPS Marubun Lokkung in 2025 is 35 people. The research respondents were the entire population of Sunday school children aged 8-11, totaling 35 people, so this research was population research. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value of rcount=0.587>rtable=0.334 shows that there is a positive relationship between Sunday school material and Sunday school behavior at GKPS Marubun Lokkung in 2025. b) Regression equation. c) The determination test revealed that the magnitude of the effect was 34.46%. d) Hypothesis testing obtained Fcount=16.946>Ftable=3.32 so H0 is rejected and Ha is accepted. The research concluded that there was a positive influence between Sunday school materials on Sunday school behavior at GKPS Marubun Lokkung in 2025.